Brand Value on the Ukrainian Dairy Market: Innovative Assessment Methodology and Development of Marketing Strategies - Sak Tetiana; Lialiuk Alla; Mylko Inna; Savchuk Yaroslava (ECONOMICS)
The article explores the conceptual foundations of building an effective brand. The BAV model is considered as a modern practical approach to brand valuation, its four key components are described. The methodology of the Interbrand company and its elements are studied. A model of dependence of brand value on loyalty and recognition indicators is proposed. Indicators that reflect the complex nature of loyalty and recognition indicators are defined. The author’s methodological approach to assessing brand value is described, which involves conducting a survey of representatives of the target audience of the studied brands, forming a database for brand evaluation, calculating the values of partial indicators, calculating the integral indicator of loyalty/recognition. The quantitative criteria for selecting brand strategies in the matrix «Loyalty-recognition (L/R)» are determined. Depending on the values of the integrated indicators - loyalty and recognition - the matrix «L/R» is proposed, which allows to choose marketing strategies for brand development. The following marketing strategies are proposed in the matrix: expanding awareness, building a brand, preserving and protecting brand positions, and building loyalty. The key elements of the proposed marketing strategies are described. The article conducts a thorough analysis of the Ukrainian dairy market, identifies its problems and prospects. The results of surveys to determine loyalty/recognition for the most famous dairy brands in Ukraine are presented. A matrix «L/R» has been built for them. Appropriate marketing strategies for dairy brands are proposed with basic recommendations for their development.